Preschool experiences and home learning environments of migrant children in urban China - Jing Gong; Nirmala Rao (Frontiers Media S.A., 2023)
Internal migration and urban expansion, hallmarks of rapid urbanization in China, have led to an increasing number of children with diverse backgrounds in cities. Cities now include migrants from rural and urban areas, and children from "urban villages" in addition to "urban locals". Parents of young children who migrate from rural to urban areas leave their children behind in rural areas ("left-behind" children) or take them along with them. In recent years, increasing parental migration from one urban area to another has also led to children being "left-behind" in urban areas. This study examined the preschool experiences and home learning environments of rural-origin migrants, urban-origin migrants, and rural-origin locals in comparison to urban locals, leveraging data from the nationally representative China Family Panel Studies (2012-2018) with 2,446 3- to 5-year-olds residing in urban areas. Regression model results indicated that children living in cities who held a rural household registration certificate (hukou) were less likely to attend publically funded preschools and experienced less stimulating home learning environments than urban local children. After controlling for family characteristics (i) rural-origin locals remained less likely to participate in preschool and experienced fewer home learning activities than urban locals; and (ii) there were no differences in preschool experiences and home learning environments between rural-origin migrants and urban locals. Mediation analyses suggested that the relation between hukou status and the home learning environment was mediated by parental absence. Implications of the findings are discussed.